Analisis Keberhasilan dan Kegagalan Kebijakan War on Terrorism pada masa Pemerintahan Bush : Studi Kasus Perang Amerika Terhadap Al Qaeda - , TIARA PUTRI KHAIRANI, Drs. Dafri Agussalim, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Policy of counter terrorism made by President Bush after 11 September 2001 became one of alteration moment for new direction of U.S foreign policy. After the end of communism era and cold war, terrorism becomes a new issue that arises and needs support from entire world. United States was the victim of the terrorism attack by international organization named Al Qaeda. United States asked the world to support and united against terrorism under their slogan âGlobal War on Terrorismâ. War on terrorism policy was created by President Bush few days after the attack. This policy has changed in and out of regulation and state policy. By using some instrument like politic and diplomacy, military and intelligence and also economic, this policy tried to fight against terrorism and save the world. Yet after two periods of Bush administration, War on Terrorism could be evaluated as failure or success policy. Rational choice as one of the way to evaluate level of failure and success from that policy. Besides, seeing all the factor which become the failure and success indicator could be another way in analyzing and evaluating.